Antimicrobial edible film prepared from bacterial cellulose nanofibers/starch/chitosan for a food packaging alternative - Abral, Hairul; Pratama, Angga Bahri; Handayani, Dian; Mahardika, Melbi; Aminah, Ibtisamatul; Sandrawati, Neny; Sugiarti, Eni; Muslimin, Ahmad Novi; Salit, Mohd Sapuan; R.A., Ilyas (Hindawi Publishing, 2021)
As a contribution to the growing demand for environmentally friendly food packaging films, this work produced and characterized a biocomposite of disintegrated bacterial cellulose (BC) nanofibers and tapioca starch/chitosan-based films. Ultrasonication dispersed all fillers throughout the film homogeneously. The highest fraction of dried BC nanofibers (0.136 g) in the film resulted in the maximum tensile strength of 4.7 MPa. 0.136 g BC nanofiber addition to the tapioca starch/chitosan matrix increased the thermal resistance (the temperature of maximum decomposition rate from 307 to 317°C), moisture resistance (after 8 h) by 8.9%, and water vapor barrier (24 h) by 27%. All chitosan-based films displayed antibacterial activity. This characterization suggests that this environmentally friendly edible biocomposite film is a potential candidate for applications in food packaging.